REVIEWIMPLEMENTATION OF THE DISCOVERY LEARNING MODEL IN IMPROVING STUDENT LEARNING OUTCOMES - oca rivana yosa (Teaching and General Education Studies, 2026)
Education in the modern era requires innovation in the learning process in order to keep up with the rapid development of science and technology. The learning process is no longer teacher-centered but should encourage students to actively participate in constructing their own knowledge. One of the learning models that can be applied to improve student participation and learning outcomes is discovery learning. This model emphasizes the process in which students discover concepts through activities such as exploration, observation, data collection, analysis, and drawing conclusions. This article aims to examine the implementation of the discovery learning model in improving students’ learning outcomes based on various literature sources and previous research findings. The method used in this study is a literature review by analyzing several books and scientific articles relevant to the topic. The results of the review indicate that discovery learning has a strong theoretical foundation and systematic stages, including stimulation, problem statement, data collection, data processing, verification, and generalization. The implementation of this model has been shown to increase students’ learning activities, motivation, critical thinking skills, and conceptual understanding. In addition, several previous studies also demonstrate that the use of the discovery learning model can significantly improve students’ learning outcomes because students are directly involved in the process of discovering knowledge. Therefore, the discovery learning model can be considered an effective alternative learning strategy to improve the quality of the learning process and students’ learning outcomes.